Trends in horizontal gene transfer research in Salmonella antimicrobial resistance: a bibliometric analysis - Yan, Jin; Doublet, Benoît; Wiedemann, Agnès (Frontiers in Microbiology, 2024)
Horizontal gene transfer (HGT) favors the acquisition and spread of antimicrobial resistance (AMR) genes in Salmonella, making it a major public health concern. We performed a bibliometric analysis to provide the current landscape of HGT in research on Salmonella AMR and identify emerging trends and potential research directions for the future. Data were collected from the Web of Science Core Collection and limited to articles and reviews published between 1999 and 2024 in English. VOSviewer 1.6.19 and CiteSpace 6.2.R1 software were used to conduct bibliometric analysis and visualize co-occurring keywords. A total of 1467 publications were retrieved for analysis. American researchers contributed the most articles (n=310). In the meantime, Institut National de Recherche pour l'Agriculture, l'Alimentation et l'Environnement have the highest citation/publication rate of 85.6. Recent studies have focused on the application of whole genome sequencing (WGS), Salmonella quinolone and colistin resistance, and the biocontrol of Salmonella AMR. These findings provide new insights into the role of HGT and help identify new targets for controlling the spread of AMR in Salmonella populations.